Playing the self-adventure board game to increase adolescents' self-esteem - Desi Desi; Fiane de Fretes; Rosiana Eva Rayanti; Marsela Riska Raswandaru (Community Empowerment, 2024)
Competition in the field of education to become excellent, accredited, and favored has an impact on students. Indirectly, to maintain their ranking status, schools generally design various dense academic and non-academic programs, requiring students to give special attention and energy. On the other hand, parents nowadays also tend to have a competitive spirit burdened on their children. One age group particularly susceptible to this situation is teenagers. Exposure to pressure inversely proportional to students' abilities will result in them experiencing low self-esteem (LSE), which if left unaddressed, can lead to depressive and even suicidal conditions. To address LSE, a therapy called "self-adventure" board game therapy is established. This community service activity aims to improve the self-esteem of students at Satya Wacana Christian High School in Salatiga. Therapy is conducted on 57 students who are indicated to have LSE through scoring on the Rosenberg Self-Esteem Scale (RSES) questionnaire. Therapy is conducted in four sessions with a group system. At the end of the sessions, all participants entered the category of high self-esteem scores. This means that playing the self-adventure game is an effective medium for resolving LSE issues.